STUDENTS’ ABILITY IN PARAPHRASING PARAGRAPHS OF ENGLISH STUDY PROGRAM FKIP UNRI - Gusparia (JEE (Journal of English Education), 2017)
The purpose of this research is to describe the result of the study: the ability of the fifth yearstudents of English Study Program in writing. This study is a descriptive research that has only one variable that is the students’ ability in paraphrasing paragraphs is evaluated by giving the students a test in form of writing a paraphrase. This research was conducted at English Study Program FKIP-UNRI. The participants of the research were the students of the fifth semester of English Study Program of FKIP-UNRI. The researcher gathered the data in form of writing test (writing paraphrase).